2019
DOI: 10.1017/s0033291719002277
|View full text |Cite
|
Sign up to set email alerts
|

Treatment response after 6 and 26 weeks is related to baseline glutamate and GABA levels in antipsychotic-naïve patients with psychosis

Abstract: BackgroundPoor response to dopaminergic antipsychotics constitutes a major challenge in the treatment of psychotic disorders and markers for non-response during first-episode are warranted. Previous studies have found increased levels of glutamate and γ-aminobutyric acid (GABA) in non-responding first-episode patients compared to responders, but it is unknown if non-responders can be identified using reference levels from healthy controls (HCs).MethodsThirty-nine antipsychotic-naïve patients with first-episode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
79
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(91 citation statements)
references
References 57 publications
6
79
2
Order By: Relevance
“…Since we found no group-level differences in baseline metabolite levels between the remission and nonremission group and did not find any single metabolite to be predictive of clinical, functional, or cognitive outcomes, this suggests that-if present-metabolite perturbances are subtle and possibly only present in part of the UHR group. This does, however, contrast findings in a first episode cohort finding higher levels of glutamate to be related to shortterm lack of remission [50], which could be explained by some studies suggesting that glutamatergic disturbances originate in thalamus and are different as the illness progresses from UHR stages to established schizophrenia [51].…”
Section: Discussioncontrasting
confidence: 81%
“…Since we found no group-level differences in baseline metabolite levels between the remission and nonremission group and did not find any single metabolite to be predictive of clinical, functional, or cognitive outcomes, this suggests that-if present-metabolite perturbances are subtle and possibly only present in part of the UHR group. This does, however, contrast findings in a first episode cohort finding higher levels of glutamate to be related to shortterm lack of remission [50], which could be explained by some studies suggesting that glutamatergic disturbances originate in thalamus and are different as the illness progresses from UHR stages to established schizophrenia [51].…”
Section: Discussioncontrasting
confidence: 81%
“…Changes in GABA release during haloperidol exposure thus likely account for the effect of haloperidol on GABA A R availability observed herein and by others (McLeod et al, 2008). Studies of bulk tissue GABA levels in the frontal cortex of schizophrenia patients using proton magnetic resonance spectroscopy ( 1 H-MRS), however, report either no effect (Bojesen et al, 2019;Tayoshi et al, 2010) or a normalisation of elevated GABA levels (de la Fuente-Sandoval et al, 2017) following antipsychotic exposure, although this method only measures bulk tissue GABA and not synaptic levels. In contrast, rodent slice electrophysiology data suggest that D2R mediate synaptic GABA release onto pyramidal neurons in the PFC, whereby GABA release is decreased following dopamine administration (Xu and Yao, 2010).…”
Section: Discussionmentioning
confidence: 61%
“…In dorsal striatum higher glutamate levels have been found (12,13), and in left thalamus higher glutamine and glutamate levels have been reported (2,3,7), whereas a recent study did not find alterations in glutamate levels (9). Importantly, our group recently reported that thalamic glutamate levels in twins are heritable and associated with schizophrenia spectrum disorder (17) and that higher thalamic glutamate levels and lower GABA levels in dorsal ACC of antipsychoticnaïve patients were related to subsequent poor treatment outcome (7). Moreover, two other groups have reported an association between high levels of glutamate and GABA in pregenual ACC and lack of treatment response (6,9).…”
mentioning
confidence: 93%
“…A growing body of studies suggest that glutamatergic and GABAergic (gamma-aminobutyric acidergic) neurotransmission is disturbed in first-episode patients with schizophrenia or psychosis. Glutamate and GABA levels in antipsychotic-naïve or minimally treated patients have primarily been investigated in anterior cingulate cortex (ACC) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11), thalamus (2,3,7,9), and dorsal striatum (12,13) using proton magnetic resonance spectroscopy ( 1 H-MRS). These regions are part of corticostriato-thalamo-cortical networks that are believed to be dysregulated in psychotic disorders (14,15).…”
mentioning
confidence: 99%
See 1 more Smart Citation